Hydroxyapatite-Coated Titanium by Micro-Arc Oxidation and Steam–Hydrothermal Treatment Promotes Osseointegration - Xiaojun Wang; Xiaojun Wang; Lina Mei; Xuesheng Jiang; Mingchao Jin; Yan Xu; Jianyou Li; Xiongfeng Li; Zhipeng Meng; Junkun Zhu; Fengfeng Wu (Frontiers in Bioengineering and Biotechnology, 2021)
Titanium (Ti)-based alloys are widely used in tissue regeneration with advantages of improved biocompatibility, high mechanical strength, corrosion resistance, and cell attachment. To obtain bioactive bone–implant interfaces with enhanced osteogenic capacity, various methods have been developed to modify the surface physicochemical properties of bio-inert Ti and Ti alloys. Nano-structured hydroxyapatite (HA) formed by micro-arc oxidation (MAO) is a synthetic material, which could facilitate osteoconductivity, osteoinductivity, and angiogenesis on the Ti surface. In this paper, we applied MAO and steam–hydrothermal treatment (SHT) to produce HA-coated Ti, hereafter called Ti–M–H. The surface morphology of Ti–M–H1 was observed by scanning electron microscopy (SEM), and the element composition and the roughness of Ti–M–H1 were analyzed by energy-dispersive X-ray analysis, an X-ray diffractometer (XRD), and Bruker stylus profiler, demonstrating the deposition of nano-HA particles on Ti surfaces that were composed of Ca, P, Ti, and O. Then, the role of Ti–M–H in osteogenesis and angiogenesis in vitro was evaluated. The data illustrated that Ti–M–H1 showed a good compatibility with osteoblasts (OBs), which promoted adhesion, spreading, and proliferation. Additionally, the secretion of ALP, Col-1, and extracellular matrix mineralization was increased by OBs treated with Ti–M–H1. Ti–M–H1 could stimulate endothelial cells to secrete vascular endothelial growth factor and promote the formation of capillary-like networks. Next, it was revealed that Ti–M–H1 also suppressed inflammation by activating macrophages, while releasing multiple active factors to mediate osteogenesis and angiogenesis. Finally, in vivo results uncovered that Ti–M–H1 facilitated a higher bone-to-implant interface and was more attractive for the dendrites, which promoted osseointegration. In summary, MAO and SHT-treated Ti–M–H1 not only promotes in vitro osteogenesis and angiogenesis but also induces M2 macrophages to regulate the immune environment, which enhances the crosstalk between osteogenesis and angiogenesis and ultimately accelerates the process of osseointegration in vivo.